Light conditions, canopy conditions and microtopographies in the microsites of shorea curtisii saplings in a hill dipterocarp forest of the Semangkok Forest Reserve, Peninsular Malaysia - G. Singh (2016)
Light conditions, canopy conditions and microphotographies in the microsites of Shorea curtisii saplings in a hill diptyerocarp forest of the Semangkok Forest Reserve, Peninsular Malaysia. Light conditions, canopy conditions and microtopographies of natural habitats of Shorea curtisii saplings in a hill dipterocarp forest of Peninsular Malaysia were examined to determine the features of the sapling microsites. We estimated values of photosynthetic photon flux density (PPF) above 41 saplings of S. Curtisii and at 301 points systematically positioned in a 2.6 ha study plot. A computerised technique for the analysis of hemisphericak photographs was used for estimating the PPFs. The microlite types were classified from canopy conditions and microtopographies. Although PPFs on gentle slopes were signifcantly higher than on steep slopes, the densities of S. Curtisi saplings were not different between the slopes. The density of S. Curtisii saplings and the PPFs in canopy gaps were not significantly different from the values under closed canopy. Most of the PPFs at each microsite type were within the range of PPFs above the saplings of S. Curtisii, and the sapling bank was maintained at all microsite types in the study plot. It is likely that most of the microsites receive sufficient light to maintain the sapling bank of S. Curtisii.